Addressing the Effect of Mindfulness Based Stress Reduction and Mindfulness Based Approaches in Sport Injury: A Systematic Review - محمد، وارهيل عاصم; بومسالود، سوموراثاي; شرول لي، نيكول (جامعة الموصل - كلية التربية الرياضية, 2021)
إن الهدف من هذه الدراسة التحليلية هو التعرف على تأثير التأمل الواعي على المتطلبات النفسية للرياضيين المصابين بعد ممارسة التأمل الواعي عن طريق الممارسة الرسمية وغير الرسمية عبر سبع دراسات رئيسية تم تصنيفها وتلخيصها. نتيجة لذلك، ستوفر هذه الدراسة تحليلا شاملا للتطبيق النظري والعملي لبرنامج MBSR في عملية إعادة التأهيل الرياضي. تم إجراء البحث العلمي عبر Web Of Science وPubMed وScopus وCINAHL، للعثور على الأبحاث التي تم نشرها بين (2011 -2020)، وذلك باستخدام مجموعة من مفاتيح الكلمات الرئيسية بالإضافة إلى استخدام البحث اليدوي. قام الباحث الأول والثاني باستخراج البيانات ذات الصلة من الدراسات. تم استخلاص المعلومات حول تصميم الدراسة، ومجتمع الدراسة، قياس تقليل الإجهاد، مدة تطبيق البرنامج والنتائج في شكل موحد. وأسفر البحث الأولي عن الدراسات عن 240 دراسة علمية. مجموع تسع دراسات كانت قابلة للتطبيق بعد تطبيق معايير الاشتمال والاستبعاد. استخدمت معظم الدراسات في هذه المراجعة طرقا كمية واستخدمت دراستان مناهج مختلطة. استخدمت إحدى الدراسات كلا من الأساليب الكمية والنوعية، بينما استخدمت دراسة أخرى كلا من الأساليب التجريبية والكمية وقامت بتقييم كل من تحمل الألم وإدراك الألم لدى الرياضيين المصابين أثناء اختبار Cold Pressor Test. وكانت بقية الدراسات الأخرى وصفية وطبقت معظم الدراسات تقنيات MBSR أو غيرها من الأساليب القائمة على التأمل الواعي مع الرياضيين المصابين. استخدمت إحدى الدراسات تصميم دراسة مقطعية (cross-section study design). جدير بالذكر كان هناك مزيج من التصميمات المنهجية التي استخدمها الباحثون. أوضحت هذه الدراسة التحليلية نتيجة واعدة لتكييف وفعالية برنامج MBSR في إعادة تأهيل الإصابات الرياضية. وذلك من خلال ممارسة التأمل الواعي بطريقتيها الرسمية وغير الرسمية من قبل الممارسين. لا يتم استخدام MBSR فقط مع المجموعات السريرية، ولكن أيضا مع المجموعات غير السريرية. وبالتالي، فإن دمج MBSR وMBA في العلاج الرياضي من شأنه أن يساعد في معرفة القيمة العملية والمعرفية فيما يتعلق بممارسة التأمل الواعي في الرياضة." The aim of this review was to determine the effect of mindfulness on the psychological demands of injured athletes following formal and informal mindfulness practice across seven major studies that were graded and summarized. As a result, this review will provide a comprehensive examination of MBSR's theoretical and practical application in the sport rehabilitation process. The scientific search was conducted via the Web of Science, PubMed, Scopus, and CINAHL, to find research that had been published between (2011-2020). Using a combination of these groups of keywords, a manual search has also been supplemented. The first and second researcher extracted relevant data from the studies. As for the information on study design, study population, stress reduction measurement, duration of intervention, and results were extracted in a standardized form. The initial search yielded 240 articles. A total of nine studies were deemed applicable following application of the inclusion and exclusion criteria. Most studies in this review used quantitative methods and two studies used mixed approaches. One study used both quantitative and qualitative methods, whilst another study used both experimental and quantitative methods. They assessed both pain tolerance and the perception of pain in injured athletes during a Cold Pressor Test. The rest of the studies were descriptive and most of the studies applied MBSR techniques or other mindfulness-based approaches with injured athletes. One study used a cross-sectional study design. There was a mix of methodology designs that had been used by the researchers. This systematic review clarified a promising outcome to adapt MBSR into sport injury rehabilitation. This is through formal and informal mindfulness practice by practitioners. MBSR is not only used with clinical populations, but also with non-clinical populations. Thus, the integration of MBSR and MBA into sport therapy would create a valuable understanding regarding mindfulness practice in sport, in both theoretical and practical knowledge."
Keywords: علم النفس الرياضي -- الصحة النفسية -- الإصابات الرياضية -- التأمل الواعي